Data-driven offshore CO2 saline storage assessment methodology. (September 2022) - Romeo, Lucy; Thomas, Randal; Mark-Moser, MacKenzie; Bean, Andrew; Bauer, Jennifer; Rose, Kelly
Highlights: The tailored methodology accounts for changes in CO2 density and sediment behavior. The calculator accounts for unique offshore features (i.e., water depths). Domain storage estimates ranged from 0.5 to 10, 000 Gigatons of CO2 . Saline efficiency was a significant factor when calculating storage capacity. The methodology and calculator are applicable at multiple geographic scales. Abstract: The world produces approximately 50 billion tonnes of greenhouse gases annually. This is measured in CO2 -equivalents, and geologic CO2 storage has the potential to advance decarbonization and mitigate greenhouse gas emissions. New technologies to assess offshore carbon storage are needed to address resource, regulatory, and commercial needs. Although most efforts to assess storage resources focus on onshore criteria, offshore reservoirs offer significant storage potential and distinct development challenges. Potential advantages of offshore carbon storage include being further from human population centers and less potential to interact with groundwater. The U.S. Department of Energy's method for evaluating storage capacity in non-oil-bearing saline reservoirs has been enhanced to support assessments for offshore environments in the Offshore CO2 Saline Storage methodology (OCSS). This methodology applies data-driven capabilities to estimate saline storage capacity while accounting for features specific to offshore reservoirs. Features include changes in CO2 density and sedimentary differences that impact estimates of permanence and capacity. The Offshore CO2 Saline Storage Calculator mechanizes OCSS to estimate storage capacity. This paper presents the methodology and estimates for 18 geologic domains in the Gulf of Mexico. Potential storage distributions, sensitivity analyses, and the incorporation of spatial data and tools to support safe site selection are also discussed.